2011
DOI: 10.21608/jfds.2011.81994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Packaging and Storage Period on Some Physical, Chemical Characteristics ,Fatty Acid Composition ,Stability and Keeping Quality of Sunflower Oil .

Abstract: This investigation was carried out to study effect of packaging and storage period on the specific gravity at 25°C (Sp. Gr) , refractive index(R.I.),color intensity; acid value, peroxide value(P .V), thiobarbituric acid (TBA) ,iodine value (IV) ,fatty acid composition , and keeping quality of Sunflower oil. The obtained results revealed that the storage of sunflower oil at ambient temperature for nine months did not seem to have any appreciable effect on the specific gravity, while the refractive index was dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
2
0
0
Order By: Relevance
“…Between packaging materials, aluminum foil was found to be the best packaging material for storage. These findings are in agreement with those obtained by Iskander et al (2011) The interaction between storage periods and package material in Table 2 and fig 1,2 indicates that 6 month with foil package gave the highest germination percentage (85.67 %), plumul (13.83 cm), radical length (18.65cm), 100-seed weight (75.00 g), protein percentage (25.53 %) and oil percentage (45.11 %). On the other hand data showed that the lowest value of electrical conductivity obtained from seeds stored inside aluminum foil package up to 18 months compared with seeds stored in woven polyethylene package.…”
Section: -Sunflower Crop:-supporting
confidence: 93%
See 1 more Smart Citation
“…Between packaging materials, aluminum foil was found to be the best packaging material for storage. These findings are in agreement with those obtained by Iskander et al (2011) The interaction between storage periods and package material in Table 2 and fig 1,2 indicates that 6 month with foil package gave the highest germination percentage (85.67 %), plumul (13.83 cm), radical length (18.65cm), 100-seed weight (75.00 g), protein percentage (25.53 %) and oil percentage (45.11 %). On the other hand data showed that the lowest value of electrical conductivity obtained from seeds stored inside aluminum foil package up to 18 months compared with seeds stored in woven polyethylene package.…”
Section: -Sunflower Crop:-supporting
confidence: 93%
“…Increasing storage period from 6 up to 18 months significantly affected acidity percentage. These findings are in agreement with those obtained byEl-Aidy et al (2001),El-Sayed et al (2004),Simic et al (2005),Ghasemnezhad and Honermeier (2007),Iskander et al (2011) and.…”
supporting
confidence: 93%